The implications of book-tax conformity and tax change for the earnings management of Portuguese micro firms - Pais, C.; Dias, C. (Journal of International Accounting, Auditing and Taxation, 2022)
Since 2014, Portugal has a special, optional tax regime for micro firms called the simplified tax regime, which is an alternative to the general tax regime. In the simplified tax regime, income tax is a percentage of specific revenues, which could be seen as an example of lower book-tax conformity. The general tax regime is an example of higher book-tax conformity because tax income is based on accounting income. Using the tax regimes as a proxy of book-tax conformity we study the influence of the different tax regimes on earnings management, as well as whether earnings management in the general tax regime is used to achieve taxable income and reporting goals. We find that firms opting for the simplified tax regime manage earnings less than firms in the general tax regime, and they manage earnings upwards while the latter manage earnings downwards. Furthermore, we conclude that accruals with high book-tax conformity are used to decrease taxable income and those with low conformity are used to increase accounting income. This leads us to conclude that lower book-tax conformity reduces earnings management. This single country case study contributes evidence on book-tax conformity issues.